Penanaman Karakter Religius melalui Budaya Sekolah di SMAN 3 Purwokerto: Telaah Teori Konstruksi Sosial - Arifin, Helmi Yusuf; Hanif, Muh. (Universitas Muhammadiyah Magelang, 2026)
This study is motivated by concerns over the moral degradation of adolescents, making the internalization of religious values an essential need in educational institutions. The study aims to describe the processes of externalization, objectivation, and internalization of students’ religious character through schoolculture from the perspective of Berger and Luckmann’s social construction theory. A descriptive qualitative method was employed using a case study and phenomenological approach, with data collected through observation, interviews, and documentation. The findings indicate that the internalization of religious character at SMAN 3 Purwokerto is effectively implemented through routine activities such as Qur’anic literacy, congregational prayers, almsgiving, and religious organizations. Religious values are expressed by the school community, institutionalized into binding rules and traditions, and ultimately internalized by students, shaping disciplined, obedient, and responsible character traits. This study emphasizes that school culture based on social construction plays a significant role in fostering sustainable religious character development among students in public schools.